Обліково-аналітичне забезпечення управління відходами виробництва борошномельної галузі - Колісник, Олена Пилипівна (Видавничий дім «Гельветика», 2021)
Стаття присвячена актуальним питанням формування обліково-аналітичного забезпечення управління відходами виробництва борошномельної галузі. Відходи утворюються у процесі виробництва чи споживання. Вони повністю або частково втратили свої початкові споживчі властивості і не мають подальшого використання за місцем їх утворення чи виявлення. Борошномельна галузь належить до числа галузей, у яких технологія виробництва передбачає як вихід основної продукції, так і утворення достатньої питомої ваги побічної продукції та виробничих відходів. У статті проаналізовано основні підходи та напрями дослідження в сфері зернопереробного виробництва. Визначено особливості класифікації відходів виробництва. Досліджено та згруповано принципи обліку відходів при виробництві продукції борошномельними підприємствами. Важливим питанням є визначення впливу величини виробничих відходів на собівартість виготовленої продукції. Важливою умовою ефективного використання відходів виробництва є їх обов’язкове оприбуткування, оскільки це впливає на зниження собівартості виробленої продукції. Розкрито питання синтетичного обліку відходів, які утворюються на зернопереробних підприємствах. Обгрунтовано необхідність формування інформації про кількість і вартість відходів та їх види у розрізі місць виникнення відходів. Крім того, увагу приділено питанню формування інформації про види сировини, з якої отримані відходи. Для обліку руху виробничих відходів пропонується спеціальна відомість, яка представляє собою кількісний та вартісний баланс відходів борошномельного виробництва. Цей баланс містить інформацію про назву відходів, їх залишки на початок та кінець звітного періоду. Важливим питанням є оцінка виробничих відходів, при цьому вид оцінки залежить від часу здійснення цього процесу. Можна виділити такі види оцінок: оцінка при оприбуткуванні з виробництва; оцінка при відпуску у подальшу переробку на самому підприємстві; оцінка виробничих відходів при реалізації.

The article is devoted to topical issues of formation of accounting and analytical support of waste management of the flour milling industry. Waste is generated in the process of production or consumption. They have completely or partially lost their original consumer properties and have no further use at the place of their formation or detection. The flour milling industry is one of the industries in which the production technology provides for both the output of the main product and the formation of a sufficient share of by-products and industrial waste. The article analyzes the main approaches and areas of research in the field of grain processing. Peculiarities of production waste classification are determined. The specifics of accounting for returnable waste, which have the largest share in the waste of flour milling businesses, have been studied. The principles of waste accounting in the production of flour milling businesses have been studied and grouped. An important issue is to determine the impact of the amount of industrial waste on the cost of manufactured products. An important condition for the efficient use of industrial waste is its mandatory posting, as it reduces the cost of production. At the same time, it is necessary to link the process of documenting the facts of occurrence the waste with the peculiarities of production technology and technical documentation. The issue of synthetic accounting of waste generated at grain processing enterprises is revealed. The necessity of forming information about the quantity and cost of waste and their types in terms of waste generation places is substantiated. In addition, attention is paid to the formation of information about the types of raw materials from which waste is obtained. This requires a document that fully provides the management of the company with information about waste, ie provides more detailed analytical accounting. To account for the movement of industrial waste, a special statement is proposed, which is a quantitative and cost balance of waste from flour milling production. This balance contains information on the name of the waste, its balances at the beginning and end of the reporting period. The balance also contains data on the amount and value of waste that has been accounted for and used for the production of basic products, and on waste that has been used as fuel and for other own needs, or has been lost during storage or sold. An important issue is the assessment of industrial waste, and the type of assessment depends on the time of this process. The following types of assessments can be distinguished: assessment in posting from production; assessment during the release for further processing at the enterprise; assessment of industrial waste during sales.
Keywords: відходи виробництва; управління відходами; зворотні відходи; відходи борошномельної галузі; класифікація відходів; оцінка відходів; production wastes; waste management; returnable wastes; wastes of flour milling industry; waste classification; waste estimation